Current landscape of CAR-therapy for osteosarcoma and rhabdomyosarcoma - Stavrou, Maria; Nicolaou, Tatiana; Georgalli, Maria; Constantinidou, Anastasia (Frontiers in Immunology, 2025)
Osteosarcoma (OS) and rhabdomyosarcoma (RMS) are the most prevalent pediatric sarcoma subtypes of the bones and soft tissues respectively. The lack in targeted treatment approaches alongside the generally dismal prognosis in the metastatic setting render the discovery of novel therapeutic modalities for these diseases a pressing need. Chimeric antigen receptor (CAR)-therapy has emerged as an innovative strategy for cancer management with marked success in the treatment of hematological malignancies. The specific approach employs genetic engineering to redirect the specificity of immune cells, primarily T cells, through the exogenous expression of fully synthetic receptors, eventually arming them with the capacity to recognize tumor associated antigens (TAA). CAR-based treatment for OS and RMS has been under investigation in pre-clinical studies over the past few years, while the first promising results from a clinical trial have recently been published. However, the so far limited efficacy of CAR-therapy in solid tumors due to various constraining factors, such as poor CAR-T cell trafficking to the tumor, minimal tumor infiltration and reduced in vivo persistence, still needs to be properly addressed. In this mini review we focus on the most recent CAR-therapy strategies explored in OS and RMS while we briefly review the evolution of CARs through the years and highlight existing challenges in the CAR field.